Timing and Adherence Matter for Sodium–Glucose Cotransporter‐2 Inhibitors in Heart Failure - Mehmet Birhan Yilmaz; Ahmet Celik; Anil Sahin; Tugce Colluoglu; Dilek Ural; Arzu Kanik; Naim Ata; Mustafa Mahir Ulgu; Şuayip Birinci (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background It is imperative to maintain the use of sodium–glucose cotransporter‐2 inhibitors (SGLT‐2is) in patients with diabetes both after the index diagnosis of heart failure (HF) and even prior to the index diagnosis of HF. We aimed to investigate whether timing of SGLT‐2 is before the index diagnosis of HF, and second, adherence to SGLT‐2is in the form of the proportion of days covered metric matter in patients with HF and diabetes. Methods and Results All‐cause death up to 7 years were evaluated in HF with diabetes from the subgroup analysis of TRends‐HF (TRends in Heart Failure in Türkiye). Patients with HF and diabetes, who were prescribed an SGLT‐2i either before or after the index diagnosis of HF were identified, categorized according to duration of exposure before the index HF diagnosis and according to proportion of days covered after the index diagnosis of HF, and compared with nonusers. There were 1 229 833 patients with HF and diabetes in the cohort. A total of 247 987 were on an SGLT‐2i and had available timing data, and 14.06% had SGLT‐2i on board before the index HF diagnosis. Median duration of SGLT‐2i exposure before the index HF diagnosis was 417 days. Prognosis was the best among patients with diabetes who were prescribed an SGLT‐2i before the index diagnosis of HF with an exposure more than median duration. Of note, among patients who were prescribed an SGLT‐2i after the index HF diagnosis; there was a numerically graded increase in all‐cause mortality rate such that a >10% decrease in SGLT‐2i proportion of days covered was associated with a 59% increase in all‐cause death (hazard ratio, 1.21–2.09). Conclusions Regardless of time or adherence, SGLT‐2is offer a remarkable all‐cause death benefit to patients with HF and diabetes. SGLT‐2is' all‐cause death benefit for patients with HF and diabetes was greatest when it was prescribed before the HF index diagnosis. Poor adherence to SGLT‐2is was associated with worsening survival in patients with HF and diabetes following the diagnosis of index HF.